Strategic Risk Management Analysis PT Indo Tambangraya Megah, Tbk. (Case Study Period 2011-2014, Amid Declining Coal Price) - Ashidiqy, Abu Bakar; Kurniawan (Universitas Nusa Putra, 2019)
The Management Strategy in mining business companies are unique and specific study, where modern mining was started to produce massive coal in the era of Industrial Revolution in England in 18th (eight teens) century, and throughout the rest of Europe due to Industrial booming, this situation continued to all over the world along with economic growth in which country surrounding where utilization of coal and minerals are required systematically then which a called as modern mining will be exploited continue till today. Decision-makers need a technical strategy and systematic analysis tools to scan the latest trend situation and condition of natural environment business, both external and internal, then assessed it and fixed it. Wheelen, make it Four Basic Elements of Management Strategy, starting with 1) Environmental Scanning, 2) Strategy Formulation, 3) Strategy Implementation, and 4) Evaluation and Control (Monitoring) Performance. In conducting to monitoring or evaluation, measurement tools the performance of the company is essential, Wheelen describes several measuring devices such are Activity Based Costing, Traditional Financial Measures, Balance Score Card, Stake Holders and Share Holders Value. The crucial thing is Enterprise Risk Management (ERM). Research has proven that the ERM in its implementation, need risk management strategies to be able to do early detection, to the survival and sustainability of the company as part of Strategy Management.